Unveiling Ceremony of Dr. Martin Luther King, Jr. Bust in Courthouse Park - Watkins, Howard::::::::: (1988)
Special guests standing: Karen Humphrey, ?, Les Kimber, Mayor Dale Doig, Supervisor Betty Ramacher